Hubungan Penyajian Informasi Event Scooterist dengan Pemenuhan Kebutuhan Informasi Followers - Muhammad Izzati Al Ghifari; Anne Ratnasari (Bandung Conference Series: Public Relations, 2024)
Abstract. The human need for information will of course include how to fulfill information after the need for survival. Factors that become the reason why humans need information include starting from the gap between the need to meet survival needs and the need for information. The Instagram account @beatboys_id is an option for getting information on sccoterist events. The purpose of this study was conducted to determine the relationship between the presentation of information in the type of information, the attractiveness of the information, and the message style on the Instagram account @beatboys_id with meeting the information needs of followers at scooterist events. The theory used in this research is the New Media theory. This study uses quantitative research methods, with a correlational approach. Collecting data by distributing questionnaires to respondents. The statistical analysis technique uses the Random Sampling technique method. The population in this study amounted to 245, with a sample of 71 @beatboys_id followers in this study. Abstrak. Kebutuhan manusia akan informasi tentunya akan meliputi bagaimana cara memenuhi informasi setelah kebutuhan bertahan hidup. Faktor yang menjadi alasan mengapa manusia membutuhkan informasi diantaranya bermula dari kesenjangan antara kebutuhan untuk memenuhi kebutuhan bertahan hidup dan kebutuhan akan informasi. Akun Instagram @beatboys_id menjadi pilihan dalam mendapat informasi event sccoterist. Tujuan penelitian ini dilakukan untuk mengetahui hubungan penyajian informasi dalam jenis informasi, daya tarik informasi, dan gaya pesan pada akun Instagram @beatboys_id dengan pemenuhan kebutuhan informasi followers pada event scooterist. Teori yang digunakan dalam penelitian ini yaitu teori New Media. Penelitian ini menggunakan metode penelitian kuantitatif, dengan pendekatan korerasional. Pengumpulan data dengan menyebarkan kuesioner kepada responden. Teknik analisis statistic menggunakan metode teknik Random Sampling. Populasi pada penelitian ini berjumlah 245, dengan pengambilan sampel 71 followers @beatboys_id pada penelitian ini.